Framework for the Development of Social Protection Systems : Lessons from International Experience - Infante-Villarroel, Mariana (World Bank, Washington, DC, 2015)
Many countries have used social protection to achieve broader development goals, particularly on poverty reduction and inclusive growth. A wide range of social protection programs allows countries to tackle specific development constraints at national, community, and household levels; provide support to particular population groups; and enhance growth-promoting opportunities.For instance, public works programs and cash transfers are important and flexible social assistance programs that can be tailored to achieve specific objectives and adjusted to various levels of institutional capacity. They can also be implemented as national and centralized programs or delivered in a more decentralized fashion through community-driven development platforms.